4CPS-121 Impact of pharmaceutical consultations for new oral oncology agents. (2nd March 2018) - Talarmin, C; Grajozsex, M; Houari, S; Clou, E; Fillon, J; Tendjaoui, F; Grazziotin-Soares, D; Lotz, JP; Gohari, A; Debrix, I
Abstract : Background: Pharmaceutical consultations are organised in the Department of Oncology when new oral anticancer drugs are prescribed. Drug-drug interactions (DDI) and drug-food interactions are frequent with these new drugs and can produce serious adverse events (SAE). Due to the chronicity of the disease and the fact that patients are taking their medication at home, consultations and phone calls are carried out by a pharmacist. Patient education is a determinant key of clinical outcomes. Purpose: To evaluate the impact of pharmaceutical consultation (PC) in the Oncology Department. Material and methods: Physicians send patients who initiate a new oral oncology agent to the pharmacist. Information about patient background and treatments are collected from the general doctors and drugstore. In order to verify the DDI, patient history, biological tests and medication review are checked. A plan of adherence and advice for the prevention of SAE are explained to the patient. Every 15 days, phone calls to patients are also made to avoid adverse events and not only SAE. At any moment the oncologist can be notified. Results: Over a 5 month period, 16 patients have been followed, including 18 interviews and 52 phone calls. After treatment collecting, 61% of DDI were avoided during the PC. Among these interactions, 12% were contraindications, 34% warnings and 54% precautions. The average for grades 1–2 toxicity is 84%, and 16% for grades 3–4. Three patients were directed to other health professionals, and five patients came as a matter of urgency to see the oncologist after phone calls to the pharmacist. Conclusion: Clinical pharmacy consultations performed in our institution reduced the risk of DDI and improved patients' observance to treatment. Grades 3–4 toxicity is avoided as much as possible by regular phone calls and coordination with medical staff. Pharmaceutical consultation could be an unavoidable step for a better use of this new type of treatment. This resulted in better patient care. The clinical pharmacy could also influence teamwork between pharmacists and other health professionals to assist patients in improving their outcomes. In the future, this enhanced health attention resulting in better use of treatments should also contribute to a decline in healthcare costs. No conflict of interest